Peran Guru dalam Dimodifikasi Proyek Penguatan Profil Pelajar Pancasila di SDN 126 Palembang - Febriansyah Farma; Yasir Arafat; Syaiful Eddy (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines the role of teachers in implementing the Strengthening Pancasila Student Profile Project (P5) at SD Negeri 126 Palembang and its impact on fostering a positive school culture. This research aims to identify and describe the role of teachers, the challenges faced, and the solutions to overcome these challenges in the Strengthening the Profile of Pancasila Students (P5) project to enhance a positive culture at SD Negeri 126 Palembang. This research employs a qualitative descriptive method with data collection techniques through documentation, interview and literature studies. The findings indicate that teachers play a crucial role in P5 implementation, including facilitating project-based learning, guiding students in understanding Pancasila values, and creating a conducive learning environment. However, challenges such as limited teacher understanding of the Strengthening Pancasila Student Profile Project (P5) concepts, insufficient training, and a lack of parental and student involvement were identified. Proposed solutions include increasing teacher training and awareness programs, strengthening collaboration between schools and parents, and developing more innovative teaching methods. With effective the Strengthening Pancasila Student Profile Project (P5) implementation, it is expected that a generation of intelligent, character-driven students with a strong positive culture in society can be developed.